Schooling masculinities and femininities in the face of the homosexual other: experiences of gay and lesbian learners within selected schools in Gauteng, South Africa - Nel, David Norton Francis (My University, 2003)
This study provides a qualitative analysis of the experiences of selected gay and lesbian learners. Identities are viewed in terms of various de-centrings of the Cartesian subject and also as constructed in binary' oppositional categories. The focus is on how South African society and schools re/construct such identities, around sexuality, gender, level of resources in schools, and ‘race . Using Iheorv on six levels of schooling, research data showed that Gauteng schools construct masculinities and femininities that are heterosexist, misogMiisi, homophobic and focussed on economic status. Learner masculinities and femininities also construct 'race', are violent, and define themselves in the face of ‘the other . Data showed that selected gay and lesbian learners negotiate these constructions in ways that leave them empowered. In this, they have common struggles, which the>' experience in unique ways. The\' also have different micro experiences, including those stemming from their own gender, ‘race' and school's level of resources.
A dissertation submitted to the School of Education. Faculty of Humanities. University of the Witwatersrand. Johannesburg, in fulfillment of the requirements for the degree Masters in Education” Johannesburg. 2()03.